2013
DOI: 10.1021/jm400336x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Adenosine A2A Receptors and Monoamine Oxidase B by 4H-3,1-Benzothiazin-4-ones

Abstract: Blockade of A2A adenosine receptors (A2AARs) and inhibition of monoamine oxidase B (MAO-B) in the brain are considered attractive strategies for the treatment of neurodegenerative diseases such as Parkinson's disease (PD). In the present study, benzothiazinones, e.g., 2-(3-chlorophenoxy)-N-(4-oxo-4H-3,1-benzothiazin-2-yl)acetamide (13), were identified as a novel class of potent MAO-B inhibitors (IC50 human MAO-B: 1.63 nM). Benzothiazinones with large substituents in the 2-position, e.g., methoxycinnamoylamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 76 publications
1
53
0
1
Order By: Relevance
“…Moderate to large species differences have previously been described for different classes of AR antagonists 50. 59, 60 As preclinical in vivo evaluation is typically performed in rodents, mainly rats or mice, we compared affinities of the investigated 1,3‐dimethyltetrahydropyrazino[2,1‐ f ]purinediones at rat and human A 1 and A 2A ARs. Correlation plots of p K i values for both species are shown in the Supporting Information (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate to large species differences have previously been described for different classes of AR antagonists 50. 59, 60 As preclinical in vivo evaluation is typically performed in rodents, mainly rats or mice, we compared affinities of the investigated 1,3‐dimethyltetrahydropyrazino[2,1‐ f ]purinediones at rat and human A 1 and A 2A ARs. Correlation plots of p K i values for both species are shown in the Supporting Information (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Monoamine oxidase assays : The determination of MAO‐A and MAO‐B inhibition was performed using commercially available recombinant human MAO‐A and MAO‐B enzymes expressed in baculovirus‐infected insect cells (Sigma–Aldrich, M7316 and M7441) applying the commercially available Amplex Red monoamine oxidase assay kit (Invitrogen A12214). The assays were performed as previously described 59. The determination of rat MAO‐B inhibition was performed using mitochondrial‐enriched fractions from male Sprague–Dawley rat livers.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, 2‐thioxo‐2,3‐dihydroquinazolin‐4(1 H )‐ones are versatile building blocks with a cyclic thiourea moiety used commonly as intermediates toward various quinazolinone‐containing molecules, including fluquinconazole . Moreover, 2‐amino‐4 H ‐benzo[ d ][1,3]thiazin‐4‐ones are valuable small molecules that have been shown to inhibit complement C1r protease, phospholipase C‐γ, monoamine oxidase B (MAO‐B) and the adenosine receptors (AR) . Recently, Heinemann and Kostenis reported that Gue1157 and Gue1158 served as potential G protein‐coupled receptor antagonists (GPCR) with a notable disparity of efficacy for Gα i ‐mediated versus Gβγ‐mediated cellular events …”
Section: Methodsmentioning
confidence: 97%
“…There are several examples in which GPCR affinity was merged with enzyme inhibition in one molecule in bi‐functional compounds, such as adenosine A 2A affinity and MAO‐B inhibition , or CB 2 R affinity and cholinesterase (ChE) inhibition . In the following section, we describe the combination of ChE inhibition with antagonism at the histamine receptor subtype 3 (H 3 R).…”
Section: Bifunctional Ligands: Combining Che Inhibitors and H3 Antagomentioning
confidence: 99%